THE INFLUENCE OF PROBLEM-BASED LEARNING ON INNOVATION DIGITAL ECOSYSTEM STUDENTS' PROBLEM-SOLVING SKILLS - Firmansyah, Ricky; Nurhasan, Ai; Almumtarizi, Almumtarizi (Jurnal Ilmiah Didaktika, 2025)
This study aims to examine the effect of Problem-Based Learning (PBL) on students' problem-solving skills. The study uses a quantitative approach with simple linear regression analysis. The respondents involved in this study were 72 students from the EID E class at ARS University, enrolled in the Digital Innovation Ecosystem course during the odd semester of the 2024/2025 academic year. The results of the regression analysis show that PBL has a significant impact on students' problem-solving skills, with an R value of 0.851 and an Adjusted R Square of 0.720. The ANOVA test indicates that the regression model is significant (F = 183.162, p < 0.01). Furthermore, the regression coefficient for the X variable (PBL) is 0.734, indicating that every one-unit increase in the implementation of PBL will improve students' problem-solving skills by 0.734 units. Based on these results, it can be concluded that PBL is effective in improving students' problem-solving skills, and it is recommended to implement this method more widely across various disciplines.